Synchronous Winches to Lift the Ship and Distributed Control System to Distribute the Motor Loads for Marine Using CAN Protocol - R. Sundar (Institute of Advanced Engineering and Science, 2017)
A shiplift is a modern alternative for these older systems. It consists of a structural platform that is lifted and lowered exactly vertical, synchronously by a number of hoists. First, the platform is lowered underwater, then the ship is floated above the support, and finally the platform with ship is lifted and the ship is brought to the level of the harbor. The modern ship lifts use synchronous winches to hoist a ship.Our project proposes a new method to construct an automated ship lifting installation. According to this, each hoisting winch is entirely controlled by a dedicated microcontroller. All such hoists on either side of the platform are networked via CAN. This result in a distributed control system that runs all the hoists synchronously, thereby achieving precisely distributed motor loads and assuring that ships cannot slip. The project uses four such hoists to raise and lower the platform. Hoists are driven by dc motors with the microcontroller controlling the winch rotational speed. Each hoist is a CAN node on the network. In order to safely operate any shiplift, all hoists must be perfectly synchronized. Winches operate at the specified speed, regardless of load, behaving as if they are mechanically coupled together. A fifth node on the network acts as the control and monitoring unit for the entire hoisting maneuver. It has switches to start and stop the process and LCD screen to display the distribution of motor loads. The Ship lifting speed is changes according to the weight of the ship.